If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6.8(2p + 5) + -1.6(4p + 6) = 0 Reorder the terms: -6.8(5 + 2p) + -1.6(4p + 6) = 0 (5 * -6.8 + 2p * -6.8) + -1.6(4p + 6) = 0 (-34 + -13.6p) + -1.6(4p + 6) = 0 Reorder the terms: -34 + -13.6p + -1.6(6 + 4p) = 0 -34 + -13.6p + (6 * -1.6 + 4p * -1.6) = 0 -34 + -13.6p + (-9.6 + -6.4p) = 0 Reorder the terms: -34 + -9.6 + -13.6p + -6.4p = 0 Combine like terms: -34 + -9.6 = -43.6 -43.6 + -13.6p + -6.4p = 0 Combine like terms: -13.6p + -6.4p = -20p -43.6 + -20p = 0 Solving -43.6 + -20p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '43.6' to each side of the equation. -43.6 + 43.6 + -20p = 0 + 43.6 Combine like terms: -43.6 + 43.6 = 0.0 0.0 + -20p = 0 + 43.6 -20p = 0 + 43.6 Combine like terms: 0 + 43.6 = 43.6 -20p = 43.6 Divide each side by '-20'. p = -2.18 Simplifying p = -2.18
| T=24m-4m^2 | | 16=4(n+1) | | h(-4)=-5 | | ix^2-8x+30=0 | | (7x^4+xy^2)dx+(x^2y+6y^5)dy=0 | | x=172+-3x | | 8(x+6)-24=4(2x+5) | | x=172+3x | | x=172 | | -6t^2+24t+14=t | | 2x-5y=36 | | 2x-17=-17+x+2 | | -(6-(a+1))=9-(5-(2a-3)) | | 10=2(h+2) | | -9x-8=6x+1 | | b-8+2b=15 | | x-8x^3+2=0 | | 4x^2=13x^2-9 | | (19b-7)-9(2b+3)=-6 | | 5=4q-7 | | -8t^2+48t-30=0 | | 1=2b-1 | | 5x+206x+30=3 | | 19-7-9(2b+3)=-6 | | 6(1)-y=9 | | -100=0.25x | | 0=t^2+6t-9 | | 4c+5=4c+3 | | 10=lx-3l | | x^2-6x-11=-8 | | 18=3p+6 | | k-10=7 |